2014
DOI: 10.1002/2014gl061331
|View full text |Cite
|
Sign up to set email alerts
|

Investigating high‐latitude ionospheric turbulence using global positioning system data

Abstract: Statistical properties of the amplitude and phase of GPS L1 signals sampled at 50 Hz are investigated to understand the turbulent behavior of the polar region ionosphere. Wavelet detrended amplitude and phase data are used to construct the probability distribution function (PDF) of the amplitude and phase fluctuations of the signal. Turbulent behavior of the ionosphere is quantified using the skewness and kurtosis of the PDF. It is found that these two independent moments are related through a parabolic relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…The relationship between kurtosis and skewness and the associated coefficients for mirror modes in the Earth's magnetosheath is similar to those found in a wide range of turbulent environments with no apparent physical connections [ Labit et al , ; Sura and Sardeshmukh , ; Hamza and Meziane , ; Mezaoui et al , ]. Consequently, our results provide additional evidence that, despite inherently different physical processes, geophysical turbulent systems dominated by second‐order nonlinearities might hold universal statistical properties and be explained under a combined mathematical formalism.…”
Section: Resultssupporting
confidence: 82%
“…The relationship between kurtosis and skewness and the associated coefficients for mirror modes in the Earth's magnetosheath is similar to those found in a wide range of turbulent environments with no apparent physical connections [ Labit et al , ; Sura and Sardeshmukh , ; Hamza and Meziane , ; Mezaoui et al , ]. Consequently, our results provide additional evidence that, despite inherently different physical processes, geophysical turbulent systems dominated by second‐order nonlinearities might hold universal statistical properties and be explained under a combined mathematical formalism.…”
Section: Resultssupporting
confidence: 82%
“…In other studies, it has been found that the profile is parabolic centered on zero, indicating that skewness and kurtosis have an empirical quadratic relationship [44]. In relevant ionospheric studies, this is considered an indication of the local dynamics of the plasma within the scattering ionospheric layer [45]. In this work, we also investigate the skewness and kurtosis profile using the data from 2010 to 2019 of all scintillation intensities, and the profile tends to collapse to the parabolic line, which is coincident with previous studies.…”
Section: Goodness Of Fit For Different Distributionsmentioning
confidence: 94%
“…Both explanations suggest that the ionosphere at these spatial scales exhibits ‘memory’ at least on a time scale of one hour and may be predictable (Siscoe & Solomon, ). Intuitively, the spectral slope partially describes the size of scintillation‐causing irregularities (Chartier et al, ; Forte et al, ; Mezaoui et al, ; Wernik, ; Yeh & Liu, ) and we should expect a relationship between spatial size and/or irregularity lifetime and future scintillation (i.e., larger irregularities would be expected to affect a given area for periods exceeding that of smaller irregularities and/or have longer lifetimes).…”
Section: Prediction Methodsmentioning
confidence: 99%